Impact of storage time on stability and antibacterial activity of sweet corn milk kefir - Mulyaningsih Sri; Rahmawati Rizki (BIO Web of Conferences)
Sweet corn milk can be used as an alternative substrate for kefir with the addition of 10% skim milk and 2% kefir grain. No research has examined the stability of sweet corn milk kefir when stored at 4oC for long periods of time. The purpose of this study was to determine the effect of 4ºC storage on the stability and antibacterial activity of kefir milk and sweet corn against Vibrio cholerae. The sweet corn milk kefir was prepared with the addition of 10% skim milk and 2% kefir grains. It was then stored at 4 oC for one month and subjected to organoleptic test, a stability test, and was also tested for antibacterial activity. The kefir had a yellow color with a pungent, sour taste and a very sour taste in week 4. The average pH ranged from 4.35 to 3.75 and the syneresis ranged from 20.87% to 22.26%. The acid contents obtained ranged from 1.195% to 1.557%. The antibacterial activity was still present after 1 month of storage. The conclusion of this study is that storage at 4°C decreases the pH, increases the viscosity, syneresis, lactic acid content and also the inhibition zone.